2018
DOI: 10.1149/2.0171812jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Roughening of Thin-Film Platinum for Neural Probe Arrays and Biosensing Applications

Abstract: We report a method for electrochemical roughening of thin-film platinum (Pt) electrodes that increases active surface area, decreases electrode impedance, increases charge injection capacity, increases sensitivity of biosensors and improves adhesion of electrochemically deposited films. First, a well-established technique for electrochemical roughening of thick Pt electrodes (wires and foils) by oxidation-reduction pulses was modified for use on thin-film Pt. Optimal roughening of thin-film Pt electrodes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…The Au surface nanorestructuring through the ORC method has shown tremendous impacts on the surface's topological features and uniformity. In this process, a 0.1 M KCl solution was used as the background solution for all gold electrodes nanorestructuring processes as the chloride-based electrolyte solution can easily trigger the dissolution and deposition of the metal by the typical triangular voltammetry treatment [32]. All the experiments followed 30 cycles of standard ORC treatment during the fabrication.…”
Section: Orc Treatment and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The Au surface nanorestructuring through the ORC method has shown tremendous impacts on the surface's topological features and uniformity. In this process, a 0.1 M KCl solution was used as the background solution for all gold electrodes nanorestructuring processes as the chloride-based electrolyte solution can easily trigger the dissolution and deposition of the metal by the typical triangular voltammetry treatment [32]. All the experiments followed 30 cycles of standard ORC treatment during the fabrication.…”
Section: Orc Treatment and Mechanismmentioning
confidence: 99%
“…Interestingly, Bailey et al reported the incredible impact of replacing the traditional use of chloride with NaOH in Ag roughening for SERS substrate preparation, resulting in a high degree of roughness, effective for SERS screening [31]. Apart from Raman spectroscopy studies' application, which mainly uses unique plasmonic effects from the roughened substrate [32,33], the ORC-engineered conductive substrate with its vast active area is potentially applied for other sensing platforms, such as in electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the instability of electrodes is still a great challenge that needs to be tackled urgently because it leads to the frequent formation of gas bubbles throughout the electrophoresis process, especially when the electrode directly comes into contact with the mobile phase, which results in poor target resolution and affects the performance of follow-up detection. 1,2 Several conventional methods that involve isolating the electrode from the solution have been proposed to reduce this limitation. [3][4][5][6][7] In order to drive the vigorous development of electrophoresis technology, it is necessary to make use of the electrode surface interface for separation and improve the stability of the electrode in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been reported to improve the charge transfer and reduce the electrochemical impedance of Pt-Ir electrodes, typically including coating 6 – 9 and surface modification 10 , 11 . These approaches can significantly enhance the charge storage capacity and reduce the electrode impedance; however, there are also challenges limiting their practical applications, such as biotoxicity and lack of long-term stability of materials 1 .…”
Section: Introductionmentioning
confidence: 99%